Translate Self-Review (TSR) Method Based on Culturally Responsive Teaching (CRT) for Arabic Writing Learning in Higher Education - Islamiyah Sulaeman; Muassomah Muassomah; Miftahul Khaerah; Nurul Fawzani; Fatimatuz Zahroh'; Muhammad Ataya Akbarunnaja; Nadiya Avivah (Journal of Languages and Language Teaching, 2024)
Arabic writing skills at the higher education level were still experiencing stagnation, which required efforts to improve learning. This research was presented as an exploration of overcoming this problem. This research aimed to describe the application of the Translate Self-Review (TSR) method based on the Culturally Responsive Teaching (CRT) approach in arabic writing learning in higher education along with students' perceptions of this learning. This research used qualitative-descriptive method, and data was collected through questionnaire, observations, and documentation, then it was analyzed using Miles and Huberman analysis techniques. This research results highlighted that although there was a positive response from students towards the use of this method in creating an enjoyable learning experience and facilitating cross-cultural relationships, there was still a gap between theory and practice, indicating obstacles in improving Arabic writing skills in elementary-level inclusive classes. This research underlined the importance of adapting learning methods that were more appropriate to students' level of understanding and extending them to higher levels of education to obtain a more holistic picture. The TSR method based CRT approach offered potential in creating an inclusive learning environment, but needed modification to effectively meet the needs of diverse learners and improve Arabic writing skills at the higher education level.